IMPLEMENTASI PERATURAN HAK CUTI HAID PADA WAKTU KERJA DALAM HUKUM KETENAGAKERJAAN DI WILAYAH YOGYAKARTA - Elza Qorina Pangestika (Justitia et Pax, 2020)
Issues related to the elimination of menstrual leave rights for women workers is one form of modern oppression that often occurs in the work environment. Through menstruation leave, the authority of the body of women workers that they should have is transferred to the hands of the power holders in the work environment. The body is accustomed to be obedient to certain interests. Departing from the assumption that many female workers do not get menstrual leave rights, this study will propose how the implementation of the menstrual leave entitlement regulations at work time in labor law in the Yogyakarta region. The subjects of this study were female workers of working age who worked in the Yogyakarta region. The research method used is a qualitative method with data collection techniques with observation and in-depth interviews. Qualitative data analysis techniques with the stages of data reduction, data presentation and drawing conclusions. This research is expected to be useful as input for the government, employers, and workers in formulating and implementing regulations concerning menstrual leave rights.